Unveiling the Multilocus Sequence Typing (MLST) Schemes and Core Genome Phylogenies for Genotyping Chlamydia trachomatis - Patiño, Luz H.; Camargo, Milena; Muñoz, Marina; Ríos-Chaparro, Dora I.; Patarroyo, Manuel A.; Ramírez, Juan D. (Frontiers in Microbiology, 2018)
Multilocus sequence typing (MLST) has become a useful tool for studying the genetic diversity of important public health pathogens, such as Chlamydia trachomatis (Ct). Four MLST schemes have been proposed for Ct (data available from Chlamydiales MLST databases). However, the lack of a sole standardised scheme represents the greatest limitation regarding typing this species. This study was thus aimed at evaluating the usefulness of the four MLST schemes available for Ct, describing each molecular marker’s pattern and its contribution towards a description of intra-specific genetic diversity and population structure. The markers for each scheme, showed a variable power of dicrimination, exhibiting in some cases over estimation in the determination of Sequence Types (STs). However, individual analysis of each locus’s typing efficiency and discrimination power led to identifying 8 markers as having a suitable pattern for intra- specific typing. Analysing the 8 candidate markers gave a combination of 3 of these loci as an optimal scheme for identifying a large amount of STs, maximising discrimination power whilst maintaining suitable typing efficiency. One scheme was compared against core genome phylogenies, finding a higher typing resolution through the last approach. These results confirm once again that although complete genome data, in particular from core genome MLST (cgMLST) allow a high resolution clustering for Ct isolates. There are combinations of molecular markers that could generate equivalent results, with the advantage of representing an easy implementation strategy and lower costs leading to contribute to the monitoring and molecular epidemiology of Ct.